Communities of practice in workplace learningA cultural interpretation of Graduate enrollment management - C. Dean Campbell; Nadielka Bishop (Adult Education Research Conference, 2015)
This paper undertakes a cultural interpretation of the roles professional expertise and context play in workplace learning through human resource interventions with a community of post-secondary administrators at one institution. To better understand and evaluate Wenger’s (1998) concept of communities of practice, an ethnographic case study methodology explores boundaries, intersections, and learning communities in communities of practice. The project examines the value communities of practice contribute to African American administrators’ professional learning in an understudied context, Historically Black Colleges and Universities (HBCUs). Case study data define interventions as indicators of a community of practice in graduate enrollment managementa) boundaries of position; (b) constellations of communities; and (c) learning communities. Implications for the study of workplace learning in context are considered as well as implications for professional and organizational development.
Keywords: communities of practice; graduate enrollment management; workplace learning